PENGARUH PERSEPSI GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP DISIPLIN KERJA KARYAWAN DI PT BORNEO ALAM SEMESTA, DESA ADONG, MELAK, KUTAI BARAT, KALIMANTAN TIMUR - Kurniadi Ramli, Alfred Januar (MOTIVASI, 2013)
Alfred Januar Kurniadi Ramli, NPM. 08.11.1001.3509.040, The Effect of The Perception of Transformational Leadership Style to The Labor Discipline of PT. Borneo Alam Semesta, Along Village, Melak, Kutai Barat, Kalimantan Timur. Industrial Psychology Department 17 Agustus 1945 University Samarinda, Undergraduate Thesis 2013.The purpose of this research was to know the relationship between the Perception of Transformational Leadership Style to the Labor Discipline. As we know that there is a lot of problems in discipline which happened in many groups, so it will be needed a leader who can give an efforts to a better aim for those groups. The data which used by the researcher in this research comes from the book, journal, newspaper, an article, survey, an interview and electronic media.The research were done with distributing a questionnaires which has 100 questions that made from the researcher itself.Â  There are 122 respondents of the production employees (non-structural) and the overall of them is a man that comes from the company which active in the coal mining area, PT. Borneo Alam Semesta in Along village, Melak, Kutai Barat, Kalimantan Timur.Â  The data analysis uses a statistic correlation product moment technique from Pearson, and also the statistic program SPSS 18 for windows.The result of this research showed the hypotheses that submitted in this research was accepted, it means that there is a significant positive relationship between the Perception of Transformational Leadership Style to the Labor Discipline with correlation score 0,253. The higher of the Perception of Transformational Leadership style means that higher of Labor Discipline, vice versa, the lower of the Perception of Transformational Leadership style means that lower of Labor Discipline. As for the effective contribution of the Perception of Transformational Leadership Style to the Labor Discipline in PT. Borneo Alam Semesta is 6,4%.